PENGARUH BIAYA AUDIT, UKURAN PERUSAHAAN, DAN TINGKAT UTANG TERHADAP PENGUNGKAPAN HAL AUDIT UTAMA (Studi pada Perusahaan Sektor Keuangan yang Terdaftar di BEI Tahun 2022–2024) - Felita Khuriani Ardia; Endang Kiswara (Diponegoro Journal of Accounting, 2026)
This study examines the effect of audit fees, firm size, and leverage on Key Audit Matters (KAM) disclosure among financial sector companies listed on the Indonesia Stock Exchange for the period 2022–2024 within the compliance theory framework. SA 701, issued by IAPI and effective since 2022, requires auditors to disclose KAM while allowing flexibility in determining narrative depth through professional judgment, resulting in variation in disclosure practices across auditors. The independent variables are audit fees, firm size, and leverage, with auditor type, auditor rotation, and firm loss serving as control variables.This study uses secondary data comprising audited financial statements, independent auditor's reports, and annual reports. The sample was determined through purposive sampling, yielding 78 companies with a total of 234 observations over three years. KAM disclosure was measured using a word count approach. Data were analyzed using multiple linear regression with Ordinary Least Squares (OLS) estimation in EViews 13.The results show that audit fees and leverage have a significant positive effect on KAM disclosure, while firm size shows no significant effect. These findings suggest that KAM disclosure is not solely determined by compliance with SA 701, but is also shaped by engagement conditions and client characteristics that drive auditors to present longer and more detailed KAM narratives.